2018
DOI: 10.1002/adsc.201801252
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydroboration of Organic Nitriles Promoted by Aluminum Complex

Abstract: We demonstrate an efficient protocol for the chemoselective hydroboration of organic nitriles with pinacolborane (HBpin) and catecholborane (HBcat) using aluminum alkyl complex [k 2 -{2-FÀC 6 H 4 NP(Se)Ph 2 } 2 AlÀ(Me)] as a pre-catalyst to afford diboryl amines under solvent-free and mild conditions (60 8C) in high yield. The aluminum complex was prepared by the reaction of [2-FÀC 6 H 4 NHP(Se)Ph 2 ] and trimethylaluminum in toluene. The solid-state structure of Al complex is established. Nitriles with a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 58 publications
(85 reference statements)
5
55
0
Order By: Relevance
“…On the basis of these experimental results and several mechanisms previously reported in the literature, the most possible mechanism for the hydroboration of carbodiimide with HBpin catalyzed by aluminum hydride complex is shown in Scheme (left). Taking compound 1 as an example to describe the mechanism, compounds 2 – 4 , belonging to aluminum hydride compounds, have the same catalytic mechanism as that of compound 1 .…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…On the basis of these experimental results and several mechanisms previously reported in the literature, the most possible mechanism for the hydroboration of carbodiimide with HBpin catalyzed by aluminum hydride complex is shown in Scheme (left). Taking compound 1 as an example to describe the mechanism, compounds 2 – 4 , belonging to aluminum hydride compounds, have the same catalytic mechanism as that of compound 1 .…”
Section: Resultsmentioning
confidence: 57%
“…Catalytic aluminum hydride compounds 2, 3,a nd a reported pre-catalyst aluminuma lkyl compound 5 were used for the hydroboration of carbodiimides. Based on the results mentioned above,t oe nsure maximum efficiency and selectivity,1 .1 equivalents of HBpin were used in neat conditions at (2), Al(1)ÀN(2) 1.860(2), Al(1)ÀN(3) 1.863 (2), Al(1)ÀN (4) 2.090(2), N(2)ÀC (6) 1.450(3), N(3)ÀC(24) 1.448 (4);N(2)-Al(1)-N(3)124.35 (11), N(1)-Al(1)-N(4) 171.24(10), N(3)-Al(1)-N(4) 81.40 (8), N(2)-Al(1)-N(1)81.27 (8). Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, efficient transition-metal-free dihydroboration of nitriles has been achieved with main group element catalysts based on Li, [40] Davit Hayrapetyan was born and raised in Armenia. Mg, [41,42] B, [43] Al [44][45][46][47][48] and Zn [49] systems. All these reports are discussed below with an emphasis on advantages and limitations of hydroboration methods, experimental conditions, substrate scope and functional group tolerance.…”
Section: Transition Metal Catalysts 21 Early Attempts: Mo-catalyzedmentioning
confidence: 99%
“…[56,57] The majority of main group metal systems developed for hydroboration of nitriles concern aluminum catalysts. [44][45][46][47][48] Thus, the first example of such transformations was reported in 2018 by Cowley and Thomas et al, who employed LiAlH 4 as a precatalyst for a series of hydroborations of alkenes, alkynes and ketones with HBPin. Within the scope of these catalytic trials, the authors also reported hydroboration of 4-trifluoromethylbenzonitrile proceeded with full conversion within 6 h at room temperature using 1 mol% of LiAlH 4 .…”
Section: Main Group Metal Catalystsmentioning
confidence: 99%